2020
DOI: 10.1186/s40659-020-00286-3
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of long non-coding RNA HOTAIR reverses cisplatin resistance of ovarian cancer cells through inhibiting miR-138-5p-regulated EZH2 and SIRT1

Abstract: Background: Cisplatin resistance (DDP-resistance) remains one of the major causes of poor prognosis in females with ovarian cancer. Long non-coding RNAs (lncRNAs) have been shown to participate in the regulation of cellular processes, including chemoresistance. The aim of this study was to explore the role of HOX transcript antisense RNA (HOTAIR) in DDP-resistant ovarian cancer cells. Methods: DDP-resistant ovarian cancer cell lines (SKOV3/DDP and A2780/DDP) were established. Real-time PCR, western blot, dual-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 39 publications
0
45
0
1
Order By: Relevance
“…It, in turn, can directly regulate the expression of EZH2 and SIRT1, which have been proven to be involved in the regulation of cisplatin resistance in ovarian cancer [ 161 ]. In addition, other miRNAs (such as miR-34a and miR-454) can be involved in regulating the chemosensitivity of ovarian cancer through the functional interaction with HOTAIR [ 118 ]. HOTAIR plays an important oncogenic role in cervical cancer, promoting the proliferation, migration, and invasion of cancer cells.…”
Section: Hotair and Micrornas Interaction In Cancermentioning
confidence: 99%
“…It, in turn, can directly regulate the expression of EZH2 and SIRT1, which have been proven to be involved in the regulation of cisplatin resistance in ovarian cancer [ 161 ]. In addition, other miRNAs (such as miR-34a and miR-454) can be involved in regulating the chemosensitivity of ovarian cancer through the functional interaction with HOTAIR [ 118 ]. HOTAIR plays an important oncogenic role in cervical cancer, promoting the proliferation, migration, and invasion of cancer cells.…”
Section: Hotair and Micrornas Interaction In Cancermentioning
confidence: 99%
“…The axis HOTAIR/miR-200c/SNAIL (or SNAI1, zinc finger transcription factor), involved in OvCa invasion, was demonstrated using transduced lentivirus-miR-200c, gain- or loss-of-function assays, EMT markers, and tumorigenicity of SKOV3 cells in xenograft tumor studies [ 118 ]. In recent work, it was shown that miR-138-5p could directly bind to HOTAIR and 3’-UTR of EZH2 (enhancer of zeste homolog 2, a histone-lysine N-methyltransferase) and SIRT1 (NAD-dependent deacetylase sirtuin 1), which was validated by the dual-luciferase reporter assay [ 119 ]. Moreover, using cisplatin-resistant OvCa cell lines, it was shown that HOTAIR reduces cisplatin chemosensitivity of OvCa cells via the axis HOTAIR/miR-138-5p/EZH2 (SIRT1) [ 119 ].…”
Section: Oncogenic Lncrnas As Cernas In Ovarian Cancermentioning
confidence: 99%
“…For lncRNA THOR, as well as for LINC00346, there is only one piece of evidence for each which demonstrates that their high expression is linked to a reduced sensitivity to cisplatin due to increased cell stemness for THOR and the inhibition of miR-342-5p for LINC00346 [ 132 , 145 ]. For lncRNA HOTAIR, similar evidence is reported in various tumor pathologies, such as lung cancer via p21 down-regulation and ovarian cancer, by activating the Wnt/b-catenin pathway or inhibiting EZH2 and SIRT1 [ 133 , 134 , 135 , 136 ]. There is no evidence in the literature on the interaction between cisplatin and the other lncRNAs with the role of oncogene reported in Table 3 .…”
Section: Role Of Ncrnas In Csccmentioning
confidence: 52%